The Role of Digital Marketing in the Growth of E-Commerce Business in India: An Empirical Study - Agasti, Biswa Ranjan (Digital Repository of Theses, 2026)
The study investigates how digital marketing strategies contribute to the expansion, competitiveness, and profitability of e-commerce enterprises in India. The primary objective is to assess the effectiveness of diverse digital marketing channels—such as social media marketing, search engine optimization, content marketing, email marketing, influencer collaborations, and paid advertising—in enhancing customer acquisition, engagement, and retention. Guided by theoretical frameworks including the Technology Acceptance Model, Diffusion of Innovation Theory, and Integrated Marketing Communications Theory, the study adopts an empirical research design using both primary and secondary data sources. Quantitative and qualitative analyses were conducted through surveys, case studies, and statistical interpretation of marketing performance indicators. Key findings reveal that digital marketing has significantly influenced e-commerce growth in India by improving brand visibility, enabling data-driven decision making, and facilitating personalized consumer experiences through artificial intelligence and analytics. Social media and mobile marketing emerged as the most influential tools in driving consumer interaction and purchase behaviour, while search engine optimization and content marketing enhanced brand authority and organic traffic. Despite these advantages, challenges such as rising customer acquisition costs, data privacy concerns, and rapid technological changes persist. The implications of this study are multifold: it offers valuable insights for policymakers to strengthen digital infrastructure and consumer protection, provides marketers with evidence-based strategies for optimizing campaigns, and guides e-commerce firms toward sustainable growth through innovation and ethical digital practices. Ultimately, the study concludes that digital marketing is not merely an auxiliary function but a central driver of India’s e-commerce transformation and a cornerstone of its digital economy.